Pemasaran Online Dalam Meningkatkan Daya Tahan dan Volume Penjualan Di Era Pandemi Covid 19 - Laurensius Tri Andy; Poppy Ruliana (Jayapangus Press, 2022)
The problems in research this is how described online marketing strategies to improve its durability and the sales volume in the covid 19.This study attempts to described online marketing strategies to improve its durability and the sales volume in the covid 19. Concept used in this research was marketing, communication social media intagram, model SOSTAC. Research methodology used is the qualitative descriptive. Data collection is done through the observation, in-depth interviews with key informants the a shopkeeper customers products online and buyers Toko Pernah Trendy. Next, study and the tracing of documentation over the internet for obtain information or data relating to the study. Data analysis used in this research was reduction, display, and verfikasi / conclusion.Research online with marketing strategies describe that uses the media instagram, shows that Toko Peernah Trendy to survive and to the sales volume increased. The findings research was social media used not only the instagram, but the press social whatsapp and line, tokopedia to sell it cooperates with Toko Pernah Trendy.